A novel random terpolymer for high-efficiency bulk-heterojunction polymer solar cells. Issue 4 (12th January 2017) - Bang, Su-Mi; Kang, Sungkyoung; Lee, You-Sun; Lim, Bogyu; Heo, Hyojung; Lee, Jaechol; Lee, Youngu; Na, Seok-In
Abstract : A new random terpolymer, coded LGC-D013, based on TPD as the acceptor and BDT and terthiophene as the donor units, has been synthesized and characterized for donor material in bulk-heterojunction (BHJ) organic photovoltaic (OPV) application. Abstract : A new random terpolymer, coded LGC-D013, based on N -alkylthieno[3, 4- c ]pyrrole-4, 6-dione (TPD) as the acceptor and benzodithiophene (BDT) and terthiophene as the donor units, has been synthesized and characterized as a donor material in bulk-heterojunction (BHJ) organic photovoltaic (OPV) applications. The thermal, optical, and electrochemical properties of the LGC-D013 were characterized. The polymer has a deep highest occupied molecular orbital (HOMO) level of −5.56 eV and an optical band gap of 1.84 eV in film. The OPV based on LGC-D013:PC71 BM blend film demonstrated a power conversion efficiency (PCE) of 6.09%, with a relatively high fill factor (FF) of 72.55%. After 1, 8-diiodooctane (DIO) treatment with a 3% volume ratio, the short circuit current density ( J sc ) was improved from 9.48 to 11.29 mA cm −2, and FF was improved from 72.55 to 73.13%, resulting in PCE improvement from 6.09 to 7.22%. The BHJ OPV using LGC-D013 as the donor polymer based on TPD and BDT with terthiophene showed an improved fill factor as high as 72%, which is higher than those of conventional TPD–BDT based polymers.